Bioimpedance-assessed muscle wasting and its relation to nutritional intake during the first week of ICU: a pre-planned secondary analysis of Nutriti Study - Cristian Deana; Jan Gunst; Silvia De Rosa; Michele Umbrello; Matteo Danielis; Daniele Guerino Biasucci; Tommaso Piani; Antonella Cotoia; Alessio Molfino; Luigi Vetrugno; Nutriti Study Group (Annals of Intensive Care, 2024)
Abstract Background Muscle mass evaluation in ICU is crucial since its loss is related with long term complications, including physical impairment. However, quantifying muscle wasting with available bedside tools (ultrasound and bioimpedance analysis) must be more primarily understood. Bioimpedance analysis (BIA) provides estimates of muscle mass and phase angle (PA). The primary aim of this study was to evaluate muscle mass changes with bioimpedance analysis during the first 7 days after ICU admission. Secondary aims searched for correlations between muscular loss and caloric and protein debt. Methods Patients with an expected ICU-stay ≥ 72 h and the need for artificial nutritional support were evaluated for study inclusion. BIA evaluation of muscle mass and phase angle were performed at ICU admission and after 7 days. Considering the difference between ideal caloric and protein targets, with adequate nutritional macronutrients delivered, we calculated the caloric and protein debt. We analyzed the potential correlation between caloric and protein debt and changes in muscle mass and phase angle. Results 72 patients from September 1st to October 30th, 2019 and from August 1st to October 30th, 2021 were included in the final statistical analysis. Median age was 68 [59–77] years, mainly men (72%) admitted due to respiratory failure (25%), and requiring invasive mechanical ventilation for 7 [4–10] days. Median ICU stay was 8 [6–12] days. Bioimpedance data at ICU admission and after 7 days showed that MM and PA resulted significantly reduced after 7 days of critically illness, 34.3 kg vs 30.6 kg (p < 0.0001) and 4.90° vs 4.35° (p = 0.0004) respectively. Mean muscle loss was 3.84 ± 6.7 kg, accounting for 8.4% [1–14] MM reduction. Correlation between caloric debt (r = 0.14, p = 0.13) and protein debt (r = 0.18, p = 0.13) with change in MM was absent. Similarly, no correlation was found between caloric debt (r = -0.057, p = 0.631) and protein debt (r = -0.095, p = 0.424) with changes in PA. Conclusions bioimpedance analysis demonstrated that muscle mass and phase angle were significantly lower after 7 days in ICU. The total amount of calories and proteins does not correlate with changes in muscle mass and phase angle.